2016
DOI: 10.1186/s41018-016-0011-y
|View full text |Cite
|
Sign up to set email alerts
|

Documenting the complex relationship between self-efficacy, resiliency, and workplace empowerment: a case study of humanitarian workers in Palestine

Abstract: There remains a critical gap in understanding challenges faced by humanitarian workers who may be key in providing assistance during complex emergencies. This study examines self-reported views by humanitarian workers working in Palestine concerning three concepts: resilience, generalized self-efficacy, and importance of workplace empowerment. Aid workers in Palestine face unique obstacles placed on economic, social, and political autonomy imposed by Israeli policy. Data obtained from 46 humanitarian workers r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
1
1
0
Order By: Relevance
“…The results also revealed that the conflict has inflicted many lifelong disabilities secondary to bullets shots, and psychological trauma in those who have experienced destruction, atrocities, and threats to life, leaving a devastating impacts on their wellbeing throughout their lives. A similar finding was reported in a previous study done among young Liberian refuges where participants reported, how the scenes of abductions, killings, seeing dead bodies, and wounded people constantly haunted them in their lives [ 39 , 40 ]. Consistent with previous studies the current study also showed that, the conflict disrupted the provision of many health promotion and preventive services including immunization and PMTCT; hence, its full impact is yet to be determined [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 87%
“…The results also revealed that the conflict has inflicted many lifelong disabilities secondary to bullets shots, and psychological trauma in those who have experienced destruction, atrocities, and threats to life, leaving a devastating impacts on their wellbeing throughout their lives. A similar finding was reported in a previous study done among young Liberian refuges where participants reported, how the scenes of abductions, killings, seeing dead bodies, and wounded people constantly haunted them in their lives [ 39 , 40 ]. Consistent with previous studies the current study also showed that, the conflict disrupted the provision of many health promotion and preventive services including immunization and PMTCT; hence, its full impact is yet to be determined [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have confirmed the link between self-efficacy of workers in humanitarian settings and their overall resilience. For example, a study of Palestinian humanitarian workers found that higher self-efficacy among workers exposed to repeated traumatic events was associated with overall higher resiliency scores ( Bonnan-White and Issa, 2016 ). Self-efficacy has also been linked to health workers’ ability to manage work related stress and avoid exhaustion.…”
Section: Discussionmentioning
confidence: 99%